THE INFLUENCE OF TRADITIONAL MEDICINE ON THE HEALING OF CHRONIC DISEASES - Gunawan Widjaja (Jurnal Kesehatan, 2024)
Chronic diseases are becoming a global health challenge, with their increasing prevalence and impact on patients' quality of life. Traditional medicine, which has been used for thousands of years in various cultures, offers potential for integration with modern medicine in managing these conditions. This study aimed to assess the effectiveness of traditional medicine in curing chronic diseases through a comprehensive literature review. The results showed that there is positive evidence regarding the effect of traditional medicine on the healing of chronic diseases. The use of medicinal herbs can significantly reduce blood sugar levels in diabetic patients, while acupuncture is effective in reducing pain severity in diseases such as arthritis. Massage therapy and meditation techniques showed a positive impact in reducing stress, which is an important risk factor for many chronic diseases. The study also found that the integration of traditional medicine with conventional care can provide a more holistic and personalized approach to chronic disease management, improving patients' quality of life.